2003
DOI: 10.1001/archfaci.5.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pericranial Skull Adherence During Healing in the Rabbit Model

Abstract: Background:The endoscopic brow-lift is a popular technique for rejuvenation of the aging brow and forehead. Long-lasting results depend on readherence of the pericranium to the underlying skull in the newly elevated position. Determination of the time required for pericranial readherence to occur is important when considering optimal brow fixation time postoperatively; however, few studies of pericranial healing exist in the literature.Objective: To quantify the time required for pericranial adherence after pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Myoplasty is not intrinsic to either of these procedures, so it is reasonable to assume that longevity of elevation is caused by healing of the periosteum to bone at the new, elevated position, counterbalanced by differential ptosis of the more superficial tissues. Sclafani and colleagues [10] previously showed that the bone-periosteum bond is well established by 6 weeks in an animal model, whereas others have described faster time courses [11,12]. In light of this report, late loss of elevation presumably would be caused by resorption of tines that are engaging tissue above the periosteum (eg, retro-orbicularis oculi fat or galeal fat [brow], suborbicularis oculi fat or malar fat [midface]).…”
Section: Discussionmentioning
confidence: 83%
“…Myoplasty is not intrinsic to either of these procedures, so it is reasonable to assume that longevity of elevation is caused by healing of the periosteum to bone at the new, elevated position, counterbalanced by differential ptosis of the more superficial tissues. Sclafani and colleagues [10] previously showed that the bone-periosteum bond is well established by 6 weeks in an animal model, whereas others have described faster time courses [11,12]. In light of this report, late loss of elevation presumably would be caused by resorption of tines that are engaging tissue above the periosteum (eg, retro-orbicularis oculi fat or galeal fat [brow], suborbicularis oculi fat or malar fat [midface]).…”
Section: Discussionmentioning
confidence: 83%
“…Troilius [9] concluded that subperiosteal lifts achieve more permanent fixation because the inelastic periosteum adheres to bone, compared with the elastic galea/ frontalis, which can descend. Healing time of periosteum to bone has been documented and ranges from 7 days to 6 to 12 weeks [33][34][35][36][37]. However, we feel that the galeal layer adheres to the periosteal layer more rapidly than periosteum heals to bare bone, thus providing an additional advantage to the subgaleal plane of dissection.…”
Section: Discussionmentioning
confidence: 83%
“…Kriet et al 18 studied the tensile strength of pericraniumcutaneous flaps using a tensiometer in rabbits that did not receive periosteal fixation, and observed a decrease in tension starting on day 3 postoperatively and a recovery by day 8 postoperatively, which remained until the last measurement on day 28 postoperatively.…”
Section: Discussionmentioning
confidence: 99%